ANALYSIS OF GRAPHIC AGITATION TECHNIQUE IN THE POSTERS OF HENRY TOMASHEVSKY AND JAN LENICA - СІЛОГАЄВА, В. В. (Art and Design, 2022)
Purpose: generalization of information about the peculiarities of graphic agitation in the posters of Henryk Tomaszewski and Jan Lenitz. Methodology. The research a «secondary research» and the method of formal analysis were used. Results. Focusing on the study of graphic agitation of Polish posters, the external and internal influences on the work of leading artists of the Polish school of posters were analyzed; highlights the main milestones of the creative path of the founders of the «Polish school»; determined what techniques and techniques were reflected in the graphic agitation of posters. The works of G. Tomashevsky, J. Lenits and the design features of their posters, the main methods of graphic agitation are analyzed. Scientific novelty. The influence of a number of circumstances on the development of poster art is reflected, and the specificity of graphic propaganda in the posters of G. Tomashevsky, J. Lenits is analyzed. Practical significance. The research will contribute to a thorough study of the artistic phenomenon – the «Polish school of posters» and graphic agitation in the posters of its founders. This, in turn, will contribute to the development of creative and artistic thinking of applicants for higher education in the Graphic Design program.